Designing of nanosized bioflavonoids using biodegradable polymeric nanoparticles by Plackett Burman method (International Current Pharmaceutical Journal, 2017)
In this present study, dual loaded flavono nanoparticulate systems have been developed for oral delivery of Naringin and Hesperidin to enhance its antioxidant and antidiabetic activities. The fabrication of Dual Loaded Flavono Nanoparticles by suitable method was optimized by Plackett Burman method. Optimization of the formulation requires proper designing of the experiments. For this reason, only in our current study, the placket burman method has been projected for the formulation of nanoparticles biodegradable polymers encompass bioflavonoid isolates for the antidiabetic activity. Ten critical parameters influencing the formulation has been selected and designed in Plackett Burman method of experimentation for 12 runs to assess independent variables influencing the result outcome. The results revealed that the 9th run shows the optimum particle size of 126.1 nm with zeta potential of 29.9 mV. Remarkably significant nanoparticles were obtained by exploiting the Plackett Burman method as designing tool.Loganathan and Sellappan, International Current Pharmaceutical Journal, January 2017, 6(2): 9-15http://www.icpjonline.com/documents/Vol6Issue2/01.pdf